Imatinib mesylate in desmoplastic small round cell tumors. (June 2017) - De Sanctis, Rita; Bertuzzi, Alexia; Bisogno, Gianni; Carli, Modesto; Ferrari, Andrea; Comandone, Alessandro; Santoro, Armando
Aim: To investigate the possible role of imatinib, an inhibitor of the tyrosine kinase activity of PDGF-R, in desmoplastic small round cell tumor (DSRCT).Patients & methods: From August 2005 to June 2009, DSRCT patients refractory to conventional treatment were enrolled. Patients received imatinib 400 mg daily. Primary end point of this open label, prospective, Phase II trial was objective response rate.Results: Of the 13 enrolled patients, eight were evaluable for response. Median age was 20 years (range: 9–32). Objective responses at 3 months were: stable disease in one patient and progressive disease in seven patients.Conclusion: Imatinib showed no efficacy in the treatment of DSRCT unresponsive to conventional therapy, despite molecular-based selection of patients.